TINJAUAN FILOLOGIS TERHADAP TEKS DEWI MANDAPA DI DALAM BABAD SUTAJAYA - Tarka Sutarahardja (IAIN Syekh Nurjati Cirebon, 2018)
AbstractThe text of Dewi Mandapa is one of the texts present in Babad Sutajaya. As a script originating from coastal areas, this chronicle is written in Javanese script (Cacarakan) by (Javanese) Cirebonan (language) in manufacturer's paper base. This text tells about the process of decline of the Sultanate of Cirebon caused by the desire of kings outside Java who wanted a girl named Rara Panas. Rara Panas is a child of Dewi Mandapa who has the pain of the death of his father by Sultan Cirebon. In an attempt to engage in text editing of Dewi Mandapa's text in this chronicle, the study is based on philological studies. To understand the content of text, a review takes the basis of traditional historiographic concepts. Based on the study conducted, the researcher got the description of Cirebon's regression process related to the existence of foreign powers in the archipelago. In fact, in the process of conquest of Cirebon, the foreign party cooperated with one of the native rulers named Raja Macan who was mistaken by Sultan Cirebon as “sato bisa muwus.”Keywords: Dewi Mandapa, regression, Cirebon